1935
DOI: 10.3181/00379727-32-7940c
|View full text |Cite
|
Sign up to set email alerts
|

Pour Plate Study of Bacteriophage

Abstract: A simple method for direct and accurate enumeration of bacteriophage is still lacking. In many instances it is desirable to determine the bacteriophage unit directly. For this purpose 2 general methods are now in use, (1) the counting of plaques formed when bacteriophage and susceptible bacteria are spread on the surface of agar plates, and ( 2 ) the determirution of the highest dilution in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1941
1941
1945
1945

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…lactic cultures used in Gorgonzola cheese was caused by bac teriophage infection. In 1955, Kiuru and Tybeck (47) Several reports in the literature have shown that the number of plaques obtained from a given bacteriophage suspen sion may vaury considerably as the result of changes in the details of the enumeration technique (1,15,17,18,34,43,48,105). Increasing the agar concentration or the thickness of the agar overlayer materially reduced the number of countable plaques (16,17,42,48).…”
Section: Historical Reviewmentioning
confidence: 99%
“…lactic cultures used in Gorgonzola cheese was caused by bac teriophage infection. In 1955, Kiuru and Tybeck (47) Several reports in the literature have shown that the number of plaques obtained from a given bacteriophage suspen sion may vaury considerably as the result of changes in the details of the enumeration technique (1,15,17,18,34,43,48,105). Increasing the agar concentration or the thickness of the agar overlayer materially reduced the number of countable plaques (16,17,42,48).…”
Section: Historical Reviewmentioning
confidence: 99%
“…It does, however, reveal plaque details of the phage not apparent in surface plaques. After the experimental work had been concluded, a paper by Yen (1934) came to our attention. Applying a very similar technique to the morphological study of phages lysing the intestinal organisms, this investigator found it very helpful and recorded findings similar to the ones given in the present report.…”
mentioning
confidence: 99%
“…Multiplicity of phage; "There seems to be no reason able doubt that there is not one phage but many phages, each possessing individual characteristics which xinder set condi tions are fairly constant and which vary v/idely between phages. Yen (1935) found that the nvimber of visible plaques differed within 10% when the agar concentration used varied from 0.5 to 2.095, but that 5^ agar would prevent the formation 16, of plaques. He found that the slower the rate of bacterial growth, the smaller the size of the plaques.…”
mentioning
confidence: 94%